The Impact of the Seven Principles of Good Practice as a Teaching Technique on EFL Student -Teachers' Performance - Sawsan Saud Aziz (College of Education for Women, 2021)
The interest in pre-service teacher training has become influential in teaching English as a foreign language, and the purpose of this training course is to prepare qualified teachers to teach effectively through the application of this technique by undergraduate students. This research aims to find out the effect of using the seven principles of good practice as a teaching technique on the fourth stage student-teachers' performance at the College of Education for Women/University of Baghdad, during the academic year 2017-2018. The sample includes (60) students selected according to the stratified sampling method. The observational checklist used by the department to assess the student teachers' performance during the practicum period is used as a study instrument.  This quantitative study used the quasi-experimental design of two independent samples, experimental control groups and the control group trained traditionally. The former group is designed to verify the hypothesis that states, "there is no statistically significant difference between the mean scores of the experimental group trained by seven principles of good practice and that of the control group trained traditionally in their teaching performance". The study has concluded that the hypothesis is rejected according to the result of the T-test of two independent samples. Accordingly, the researcher recommends the university administration to use new techniques in learning and overcoming the difficulties that the student teachers face and the shortcoming encountered during the educational process.